Seeing is believing – healthcare professionals' perceptions of a complex intervention to improve care towards the end of life: A qualitative interview study. (February 2018) - Bristowe, Katherine; Carey, Irene; Hopper, Adrian; Shouls, Susanna; Prentice, Wendy; Higginson, Irene J; Koffman, Jonathan
Background: Methods to improve care, trust and communication are important in acute hospitals. Complex interventions aimed at improving care of patients approaching the end of life are increasingly common. While evaluating outcomes of complex interventions is essential, exploring healthcare professionals' perceptions is also required to understand how they are interpreted; this can inform training, education and implementation strategies to ensure fidelity and consistency in use. Aim: To explore healthcare professionals' perceptions of using a complex intervention (AMBER care bundle) to improve care for people approaching the end of life and their understandings of its purpose within clinical practice. Design: Qualitative study of healthcare professionals. Analysis informed by Medical Research Council guidance for process evaluations. Setting/participants: A total of 20 healthcare professionals (12 nursing and 8 medical) interviewed from three London tertiary National Health Service hospitals. Healthcare professionals recruited from palliative care, oncology, stroke, health and ageing, medicine, neurology and renal/endocrine services. Results: Three views emerged regarding the purpose of a complex intervention towards the end of life: labelling/categorising patients, tool to change care delivery and serving symbolic purpose indirectly affecting behaviours of individuals and teams. All impact upon potential utility of the intervention. Participants described the importance of training and education alongside implementation of the intervention. However, adequate exposure to the intervention was essential to witness its potential added value or embed it into practice. Conclusion: Understanding differing interpretations of complex interventions is essential. Consideration of ward composition, casemix and potential exposure to the intervention is critical for their successful implementation.